PENGARUH BRAND EXTENSION, POTONGAN HARGA, DAN E-SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN SHOPEEFOOD - Pahlevi, Enrico; Basuki, Ananto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Technology has developed drastically and continues to evolve until now. The number of internet users that can be said to be very high has resulted in a lot of people's consumptions depending on internet activities. The purpose of this quantitative research is to identify the effects of brand extension, price discount, and e-service quality on purchase decision. This study is categorized into explanatory research since it tries to explain the position of the variables being studied and to identify the effect of a variable on other variables through hypothesis testing. The sample of this research was selected using purposive sampling, with the criteria of having the minimum education of elementary school and made purchases at least once in a month, resulting in 169 respondents. Here validity test, reliability test, and multiple linear regression were used. This study finds that brand extension has significant effects on purchase decision. Price discount has significant effects on purchase decision. E-service quality have significant effects on purchase decision.